2009
DOI: 10.1029/2009jb006393
|View full text |Cite
|
Sign up to set email alerts
|

Evidences for strong directional resonances in intensely deformed zones of the Pernicana fault, Mount Etna, Italy

Abstract: [1] In this paper we investigate ground motion properties in the western part of the Pernicana fault. This is the major fault of Mount Etna and drives the dynamic evolution of the area. In a previous work, Rigano et al. (2008) showed that a significant horizontal polarization characterizes ground motion in fault zones of Mount Etna, both during earthquakes and ambient vibrations. We have performed denser microtremor measurements in the NE rift segment and in intensely deformed zones of the Pernicana fault at P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 76 publications
5
39
0
Order By: Relevance
“…[] too related the observation of directional ground motions on a ridge in the Apennines to large open fractures, polarization direction being transversal to the fractures. There are other cases where directional horizontal motions occur but are not controlled by topography, e.g., those observed in fault zones [ Rigano et al ., ; Di Giulio et al ., ; Pischiutta et al ., ]. In these study cases the role of topography was ruled out because of the flat study area (as in the Hayward fault zone, see Pischiutta et al .…”
Section: Discussionmentioning
confidence: 99%
“…[] too related the observation of directional ground motions on a ridge in the Apennines to large open fractures, polarization direction being transversal to the fractures. There are other cases where directional horizontal motions occur but are not controlled by topography, e.g., those observed in fault zones [ Rigano et al ., ; Di Giulio et al ., ; Pischiutta et al ., ]. In these study cases the role of topography was ruled out because of the flat study area (as in the Hayward fault zone, see Pischiutta et al .…”
Section: Discussionmentioning
confidence: 99%
“…We selected six earthquakes with M L ≥ 3.4 to check if a predominant site polarization is maintained independently of the nature of the seismic signals. Rigano et al [2008] and Di Giulio et al [2009] found that, in tectonically active zones of Etna, both volcanic tremor and earthquake‐induced ground motions tend to be markedly polarized with an orthogonal direction from the faults orientation. The selected events, listed in Table 1, are distributed at various azimuths from the summit craters (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…The difference in amplitude between the three components of all stations (the effect at EBEL is evident in Figure 2) suggests that ground motion must be polarized in the study region. This is a common feature in many areas of intense deformation on Etna [ Rigano et al , 2008; Di Giulio et al , 2009]. To investigate this feature in detail, the three component records were also used to compute the station polarization in the different eruptive phases.…”
Section: Seismic Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Del Gaudio, 2017), can be used to characterise the mechanical properties of the soil or rock mass (e.g. anisotropy, sets of directional discontinuities; Di Giulio et al, 2009) and their changes with time (e.g. shear wave velocity decrease due to crack opening or water level rise; Daskalakis et al, 2016;Behm, 2016), potentially providing an indirect assessment of strength degradation or stress changes.…”
Section: Open Discussion: the Lesson Of A Killer Landslidementioning
confidence: 99%